Comparison of Natural Fibers as Acoustic Panels - Mohd Azhar, Nor Azwa Yasmin; Wahid, Abdul Zaki Abdul (Progress in Engineering Application and Technology, 2021)
Global demand for acoustic panels has increased due to its increasing as a medium to control noise in the industry especially in improving the quality of acoustics in buildings. Therefore, this study was conducted to study the composite characteristics of acoustic panels reinforced using natural fibers. In addition, the properties of natural fibers will be studied in the effectiveness of the panel on its acoustic properties that is the coefficient of sound absorption in the building will be tested in this study. Next, this study was conducted to find alternative materials from natural materials that are 'green' to the environment and also sustainable for future generations. The objective of this study is to identify previous sound absorption coefficient study methods that study natural fiber-based acoustic panels and review on sound absorption coefficient data based on different thickness and density for each study method. The important things to have such as the collection of article material and the material studied. Pineapple leaf fiber and hemp fiber show relatively stable and high sound absorption not only in the frequency range of 500-2048 Hz but also in the high frequency range. In addition, density and thickness are very important for practical applications, as light and small-sized sound absorbers can be used more widely. Therefore, it can be concluded that pineapple leaf fiber and hemp fiber can be an ideal alternative as acoustic panels.